Pengaruh Dekokta Eceng gondok (Eichhornia crassipes) terhadap Kadar Malondialdehid (MDA) dan Nekrosis Sel Tubulus Proksimal Ginjal Tikus Wistar Jantan dengan Induksi Oral Kadmium Klorida (CdCl2) Subkronis Dosis Rendah - Wika Yuli Deakandi; Rio Risandiansyah; Arif Yahya (Published by Faculty of Medicine Universitas Islam Malang, 2017)
Introduction: Cadmium is a heavy metal pollutant which has high toxicity. Long term exposure to cadmium at low dose is able to induce kidney damage, possibly due to an increase in ROS. Water hyacinth (E. crassipes) is known to contain antioxidants that can prevent free radical damage. The purpose of the research is to investigate the effect of water hyacinth in preventing kidney damage, characterized by a decreasein MDA levels and renal proximal tubular cell necrosis of male wistar rats induced using subchronic CdCl2 at low dosage, administered orally.Methods: This is an in vivo laboratory experiments using 30 male wister rats (Rattus norvegicus), which were divided into 5 treatment groups (6 rats/groups). The negative control group was fed by standard food and drink while the positive control are treatment groups were given CdCl2 (5 mg/KgBB) orally for 28 days. The treatment groups were also given water hyacinth decocta with a dosage of 200 mg/KgBB, 400 mg/kgBB and 800 mg/kgBB for 28 days. On the 29th day of treatment, the rats have to be sacrificed and its kidney tissue were examined for histopathology and MDA.Results : Oral administration of CdCl2 (5 mg/kg) for 28 days significantly induced kidney damage which was evident from the increased levels of MDA (1,131 ± 0,135 ng/200mg ) and the proportion of necrosis of the kidney proximal tubule cells(73,189 ± 10,556 %), which was higher than the negative control group (MDA:0,179±0,021, kidney necrosis:35,777±2,593%). The addition of water hyacinth decoction at the doses of 200 mg/kg, 400 mg/kg and 800 mg/kg significantly decrease the MDA levels of kidney tissue(0,456±0,067 ng/200mg, 0,394±0,054 ng/200mg, 0,528±0,141 ng/200mg, respectively) and the percentage of proximal renal necrosis (53,729±4,875 %, 49,755±6,892%, 50,552±4,566%, respectively) compared to positive control group (MDA:1,131±0,135ng/200mg, kidney necrosis:73,189±10,556%).Conclusions: Decocta of water hyacinth at the doses of 200mg/KgBB, 400 mg/KgBB and 800 mg/KgBB were able to prevent renal organ damage due to subchronic exposure CdCl2. Keywords: Water Hyacinth, E. Crassipes, Cadmium Chloride, Subcronic, MDA, kidney necrosis